Effect of different phosphorus management practices on growth, yield and economics of summer groundnut (Arachis hypogaea L.): EFFECT OF PHOSPHORUS ON GROWTH, YIELD AND ECONOMICS OF SUMMER GROUNDNUT - RAGHAVENDRA NAGAR; RAM A JAT; R K MATHUKIA; R R CHOUDHARY; KIRAN K REDDY (Journal of Oilseeds Research, 2019)
A field experiment was conducted during summer, 2018 at Junagadh Agricultural University, Junagadh, Gujarat, to studyeffect ofimproved microbial cultures on P nutrients, growth and yield ofsummer groundnut using improved microbial cultures. The experiment was laid out in randomized block design with ten treatments, replicated thrice. The results revealed that application of 100 % RDP + FYM @ 5 t/ha was found significantly superior over rest of the treatments with respect to growth, yield and nutrient uptake. Treatments comprisingmicrobial cultures viz., 100% RDP + DGRC 1 and 100% RDP + DGRC 2 produced significantly higher number of pegs/plant, number and weight of mature pods/plant, pod and haulm yield over 100% RDP. Maximum gross returns ( 1,12,251/ha) were obtained with the application of 100% RDP + FYM @5 t/ha compared to rest of the treatments while highest net returns (`56,058/ha) and benefit-cost ratio (2.3) was gained with 100% RDP + DGRC 1.